Rapid and Simple Determination of Sarafloxacin and Difloxacin in Beef by Capillary Electrophoresis Coupled with Solid-Phase Extraction - Qian Wang; Rui Zhao; Yan Cui; Cuicui Liu; Liya Liang; Shijie Yan (Journal of Analytical Methods in Chemistry)
A simple and rapid capillary electrophoresis method with diode array detector was developed for determination of sarafloxacin and difloxacin in beef. In this study, the experimental parameters affecting the determination were systematically optimized, including wavelength, buffer system, pH and concentration, and separation temperature and voltage. Under the optimal conditions, sarafloxacin and difloxacin could be quantified within 4 min using H3BO3/Na2B4O7 buffer (35 mmol/L, pH 8.8) as background electrolyte, 25 kV as separation voltage, and 22°C as the column temperature. The linear range of the method was 1–20 μg/mL with LOD 0.8 μg/mL for sarafloxacin and 0.5–20 μg/mL with LOD 0.3 μg/mL for difloxacin. The RSDs for the peak area of 8 μg/mL sarafloxacin were 4.8% (intraday) and 7.8% (interday), respectively. The proposed method has been applied to determine the residue of sarafloxacin and difloxacin in beef samples with the satisfactory recovery.